Transmitting audio via fiber optics under nonlinear effects and optimized tuning parameters based on Co-simulation of matlab and optisystemTM - Abdulrasul A. Al-Hayder; H. J. Abd; Ahmed Samawi Alkhafaji (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Limitations of conventional wires such as copper wires are causing dispersion and distortion of the message signal for long distances communication especially for the wide bandwidths. The ability of fiber optic to overcome this problem is making it a dominant transmission medium. Despite of this major positive attribute of optic fibers, there is still a downside for using the fiber optic communication; that is the nonlinearity problem especially at the very high frequency bandwidth. For the first time, a desigen of an audio signal is suggested and executed in MatLab with an integration with OptiSystemTM software to discuss and solve this issu. The audio signal is then transmitted in different shapes of modulation signals (NRZ, RZ & RC) for different distances (100 km & 75 km) via a fiber optic media to be received in a receiving part of the simulated system. Three tests are used to do so. The first is the Quality-factor (Q-Factor) against the received power, second test is eye diagram performance and finally is the measuring of the amplitude of output (received) signal for each modulation signal shape using the Oscilloscope Visualizer. The NZR modulation signal was found to be the best one of the three used signals’ types in all three tests. The Q-factor for NRZ pulse shape (=12) was higher than that for RZ (=10) and RC (=8) for a 100 km distance at the same received power level.